Percutaneous Nephrolithotomy: Is Distilled Water as Safe as Saline for Irrigation? - Hosseini, Mohammad Mehdi; Hassanpour, Abbas; Manaheji, Farhad; Yousefi, Alireza; Damshenas, Mohammad Hassan; Haghpanah, sezaneh (Urology Journal, 2014)
Abstract Purpose: To compare dilutional effect of distilled water with saline solution as an irrigation fluid in percutaneous nephrolithotomy (PCNL). Materials and Methods: Three hundred twenty eight adult patients (191 men, 137 women) who were candidates for PCNL were randomly assigned into two groups (distilled water, n = 158, group 1; saline solution, n = 162, group 2). Stone size, operation time, irrigation fluid volume, blood hemoglobin level, urea nitrogen, creatinine, sodium and potassium levels were checked before and at 6 and 12 hours after operation. Results: The mean age of the patients was 37.8 years, and the mean stone diameter was 31.5 mm. There was no clinical case of transurethral resection (TUR) syndrome. Serum sodium depletion was significantly more in group 1 than group 2 (P < .0001). Group 1 had significant decreased post-operative serum sodium levels (P < .0003). Similarly in group 2, postoperative serum sodium levels were significantly lower than the preoperative concentration (P < .01), but it was not the same 6 hours after the operation (P = .23). Serum sodium concentrations remained within normal limits in all cases, without causing clinical signs and symptoms of hyponatremia. Conclusion: We found that distilled water is safe irrigation fluid for PCNL in adults. In addition, it is more available and cost effective.